Weight-bearing radiographs and cone-beam computed tomography examinations in adult acquired flatfoot deformity. Issue 2 (February 2021) - Shakoor, Delaram; de Cesar Netto, Cesar; Thawait, Gaurav K; Ellis, Scott J; Richter, Martinus; Schon, Lew C; Demehri, Shadpour; ,
Highlights: Moderate to very good correlation was noted between weightbearing radiographic and weightbearing CT measurements. Angular measurements were overall increased in weightbearing CT images, comparing with weightbearing radiographs. Compared to 3D weightbearing CT, weightbearing radiographs can potentially underestimate adult acquired flatfoot severity. In patients with adult acquired flatfoot, limitations of weightbearing radiographic evaluation should be considered. Abstract: Background: Optimal characterization of Adult acquired flatfoot deformity (AAFD) on two-dimensional radiograph can be challenging. Weightbearing Cone Beam CT (CBCT) may improve characterization of the three-dimensional (3D) structural details of such dynamic deformity. We compared and validated AAFD measurements between weightbearing radiograph and weightbearing CBCT images. Methods: 20 patients (20 feet, right/left: 15/5, male/female: 12/8, mean age: 52.2) with clinical diagnosis of flexible AAFD were prospectively recruited and underwent weightbearing dorsoplantar (DP) and lateral radiograph as well as weightbearing CBCT. Two foot and ankle surgeons performed AAFD measurements at parasagittal and axial planes (lateral and DP radiographs, respectively). Intra- and Inter-observer reliabilities were calculated by Intraclass correlation (ICC) and Cohen's kappa. Mean values of weightbearing radiograph and weightbearing CBCT measurements were also compared. Results: Except for medial-cuneiform-first-metatarsal-angle, adequate intra-observer reliability (range:0.61−0.96) was observed for weightbearing radiographic measurements. Moderate to very good interobserver reliability between weightbearing radiograph and weightbearing CBCT measurements were observed for the following measurements: Naviculocuneiform-angle (ICC:0.47), Medial-cuneiform-first-metatarsal-gapping (ICC:0.58), cuboid-to-floor-distance (ICC:0.68), calcaneal-inclination-angle(ICC:0.7), axial Talonavicular-coverage-angle(ICC:0.56), axial Talus-first-metatarsal-angle(ICC:0.62). Comparing weightbearing radiograph and weightbearing CBCT images, statistically significant differences in the mean values of parasagittal talus-first-metatarsal-angle, medial-cuneiform-first-metatarsal-angle, medial-cuneiform-to-floor-distance and navicular-to-floor-distance was observed (P < 0.05). Conclusion: Moderate to very good correlation was observed between certain weightbearing radiograph and weightbearing CBCT measurements, however, significant difference was observed between a number of AAFD measurements, which suggest that 2D radiographic evaluation could potentially underestimate the severity of AAFD, when compared to 3D weightbearing CT assessment.